Nasha Istoriia: The Russian Revolutions, the State, School Textbooks and Public Celebrations Under Putin. Issue 1 (2nd January 2019) - Pearce, James C.
Abstract : Russia's state and society are still coming to terms with the legacy of 1917. An underlying fear of revolutions exists due to their perceived chaos and instability. The centenary coincided with revisions of national history education under the presidencies of Vladimir Putin. These revisions are designed to project an image of a united country and strong sovereign state under the banner of patriotism. The 1917 revolutions represent a disruption in Russia's history and undermine the patriotic message in these new narratives. This article assesses the treatment of the 1917 revolutions in contemporary Russia via two media; school textbooks and public celebrations. Revisions of the national history must legitimize the state and its goals. Textbooks and commemorations are media that reflect the preferred images of the past to promote national unity, historical continuity and discourage domestic discords. Both media show the complexity in retelling the narrative of 1917. Whilst modern school history textbooks paint the revolutions somewhat negatively, few official commemorations took place in 2017. Those that did were kept at arm's length and lacked a narrative. With seemingly nothing to gain from this part of history, meaningful assessments of 1917 have been left to schoolteachers or postponed altogether.